2011
DOI: 10.1186/1471-2415-11-1
|View full text |Cite
|
Sign up to set email alerts
|

ISRCTN12125882 - Influence of topical anti-VEGF (Ranibizumab) on the outcome of filtration surgery for glaucoma - Study Protocol

Abstract: BackgroundExcessive wound healing, with scarring of the episcleral tissue or encapsulation of the filtering bleb is the main reason for failure in trabeculectomy. Ranibizumab, an inhibitor of the Vascular Endothelial Growth Factor (VEGF), is seen as a promising candidate to prevent or treat extensive wound healing. We describe the design of a two phased study, i) assessing the local tolerability and safety of topical ranibizumab and ii) assessing the efficacy of topical ranibizumab against placebo in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Currently available studies on glaucoma treatment have reported the use of anti-VEGF factors under the conjunctiva [ 13 ] and in the anterior chamber [ 7 ] and vitreous cavity [ 14 16 ], and even reported that topical eye drops containing ranibizumab (2 mg/mL) after filtering surgery can reduce the formation of bleb scarring [ 17 ]. However, there are large discrepancies in the conclusions reached by a number of small-scale clinical studies on NVG.…”
Section: Discussionmentioning
confidence: 99%
“…Currently available studies on glaucoma treatment have reported the use of anti-VEGF factors under the conjunctiva [ 13 ] and in the anterior chamber [ 7 ] and vitreous cavity [ 14 16 ], and even reported that topical eye drops containing ranibizumab (2 mg/mL) after filtering surgery can reduce the formation of bleb scarring [ 17 ]. However, there are large discrepancies in the conclusions reached by a number of small-scale clinical studies on NVG.…”
Section: Discussionmentioning
confidence: 99%
“…12 A clinical trial designed to examine the efficacy of topically applied ranibizumab eyedrops on fibrous scar formation after GFS is under way. 16 In a previous study, 17 we demonstrated that trehalose inhibited the proliferation of fibroblasts by inducing apoptosis. In rabbit GFS models, we also observed that trehalose inhibited conjunctival neovascularization in bleb areas after GFS.…”
mentioning
confidence: 87%
“…Natural language processing was used as part of a multimodal approach for extracting cataract cases from broader datasets. In a retrospective review of the Personalized Medicine Research Project (PMRP) cohort, Waudby et al 14 identified 16,336 cataract patients by combining structured database querying of CPT and ICD-9 codes, natural language processing for data mining of text-based notes, and intelligent character recognition (ICR) of handwritten notes. The results of this combined search were validated by manual extraction of each note.…”
Section: Discussionmentioning
confidence: 99%